MICROTEACHING AS TEACHING STRATEGY OF COMPUTER ASSISTED LANGUAGE LEARNING (CALL) FOR ENGLISH PRE-SERVICE TEACHERS - Azmina, Badi'atul; Fauziati, Endang; Drajti, Nur Arifah (English Department of Faculty of Tarbiyah and Teachers Training, 2018)
In order to facilitate English pre-service teachers to have ability in integrating technology in the classroom, microteaching is one of teaching strategy solutions. This present study examines how microteaching was used as teaching strategy of Computer Assisted Language Learning (CALL) for English pre-service teacher. It is case study design. The setting of this study was in one of Islamic State University in Indonesia, in the English Education Department. The data are from interview, document analysis, and observation. The result shows that the teaching strategies of Computer Assisted Language Learning (CALL) which was a microteaching consisted of lesson planning, teaching, and evaluating. Lesson planning and teaching step were done by the English pre-service teacher. Yet, the evaluating step was done by the lecturer and peer pre-service teachers. The significance of this study is for example on how to implement microteaching of Computer Assisted Language Learning (CALL) to English pre-service teachers.